Pilgrimage to Imeko (Nigeria): An African Church in the Time of the 'Global Village' - (:unkn) unknown (My University, 2002)
African Independent Churches, or AICs (to use the expression established by English-speaking missionaries), do not form a very coherent or homogeneous category The diversity of these churches stems largely from the fact that their ‘independence' has been established on the basis of an ethnic identity, which leads to churches being referred to as ‘indigenous' or ‘national', or by a split following [---] among other things [---] a refusal by the mother church to allow equality, as with the ‘separatist' churches of South Africa, or on the initiative of a prophetic revelation bearing a messianic message, or by an innovation in ritual or healing technique, where they are known as ‘prophetic churches'. Such autonomy, which is naturally viewed in relation to the hegemony of ‘white' Christian churches, is not without its ambivalence.
Keywords: African Research